2022
DOI: 10.35848/1347-4065/ac7ea9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni doping on the electro-optic property in K(Ta0.6Nb0.4)O3 films

Abstract: The rising of thin-film-based plasmonic electro-optic (EO) devices triggers considerable exploitation of ferroelectric oxide thin films with large EO response. In this study, epitaxial (001)-orientated Ni-doped K(Ta0.6Nb0.4)O3 (KTN) films were fabricated on SrRuO3/SrTiO3 substrates via pulsed laser deposition. In comparison with a pure KTN film, a larger withstand electric field was achieved by Ni doping. The EO measurements revealed that the doping of Ni ions induced a decrease in the effective EO coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…gap-state engineering, can activate the visible-light PV response. The impact of chemical doping on the optical, [155][156][157][158][159][160] structural, 161,162) and electrical [163][164][165][166][167][168][169][170][171][172][173] properties of materials has been intensively studied by many researchers. Chemical doping of conventional ferroelectric oxides such as LiNbO 3 , 2,3,76) BaTiO 3 , 75,174,175) and Pb-based perovskites 85,87,176) effectively enhances the PV response.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…gap-state engineering, can activate the visible-light PV response. The impact of chemical doping on the optical, [155][156][157][158][159][160] structural, 161,162) and electrical [163][164][165][166][167][168][169][170][171][172][173] properties of materials has been intensively studied by many researchers. Chemical doping of conventional ferroelectric oxides such as LiNbO 3 , 2,3,76) BaTiO 3 , 75,174,175) and Pb-based perovskites 85,87,176) effectively enhances the PV response.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…Ferroelectrics, which exhibit various nonlinearities in dielectric, optic, and electromechanical responses, seem to be attractive materials for physical RC. [9][10][11][12][13][14][15] Indeed, Toprasertpong et al have demonstrated the physical RC system using ferroelectric gate FETs, in which hafnium zirconium oxide ferroelectric film was employed as the gate insulator of FET. [16][17][18] Using the rich dynamics originating from ferroelectric polarization switching, computational tasks on time-series data processing, including nonlinear time series prediction, have been successfully solved.…”
Section: Introductionmentioning
confidence: 99%